The incidence of sensorineural hearing loss diagnoses in people with and without Alzheimer’s disease – a nationwide cohort study - Kaisa Hokkinen; Aarno Dietz; Pasi Lampela; Sirpa Hartikainen; Anna-Maija Tolppanen (BMC Geriatrics)
Abstract Background Sensorineural hearing loss (SNHL) is a risk factor for cognitive impairment, but little is known on whether the diagnosis of Alzheimer’s disease (AD) affects the diagnosis of SNHL. We studied the temporal changes in the incidence of SNHL diagnosis in relation to AD diagnosis. Methods This study is part of Medicine use and Alzheimer’s disease cohort (MEDALZ) study. Our nationwide register-based study included 42,934 community-dwelling persons who received a clinically verified AD diagnosis in 2008–2011 in Finland and a 1:1 matched comparison cohort. We calculated the incidence of SNHL diagnoses per 100 person-years (PY) from ten years before to five years after the date of AD diagnosis (index date). Results Before the index date, the incidence of SNHL diagnoses was higher among persons with AD (1.51/100 PY) than in the comparison cohort (1.34/100 PY, adjusted hazard ratio, 95%Cl 1.10, 1.06–1.13). After AD diagnosis the incidence was lower among persons with AD (1.05 and 1.66/100 PY, adjusted hazard ratio, 95%Cl 0.60, 0.56–0.62). The incidence increased in a similar manner in both groups before the AD diagnosis. In the AD group the incidence peaked at the index date, but steeply declined shortly after, while in the comparison cohort, it continued its previous ascending course. Conclusions The incidence of SNHL diagnosis declines after AD diagnosis, suggesting that AD may alter diagnostic trajectories and access to audiological care.